PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IIIA SD NEGERI 011 BANJAR XII KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - ', Elfiani; Kurniaman, Otang; Daud, Damanhuri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research have as a starting point of study low result students class IIIA SD Negeri 011 Banjar XII Subdistrict Tanah Putih with average class 62,50. While minimize completness criteria value ( KKM ) IPA is 70. From twenty students, only nine peoples that reach out for minimize completness clasical 45,00%. The formulation of problem research is: What application learning cooperative mode type Snowball Trhowing can increase result study IPA students class IIIA SD Negeri 011 Banjar XII Subdistrict Tanah Putih? This research of purpose for increase study result IPA students class IIIA SD Negeri 011 Banjar XII Subdistrict Tanah Putih. This research did of date 19 March until 19 April 2014 with two cycle. Subject this research is students class VB SD Negeri 011 Banjar XII Subdistrict Tanah Putih. Instrument collect data of this skripsi is observation sheet teacher activity and obsevate sheet students activity as study students result. Sheet activity teacher in learning process of cycle one first meet 58,3% (quite category) and second meet increase become 72,2% (good category). Cycle Two firts meet 86,1% (category best good) and second meet increase become 94,4% (best good category). Analiyze result data activity sheet students of cycle one first meet 55,5% (quite category) and second meet become 61,6% (good category). Cycle Two firts meet 77,7 (category good) and second meet is increase become 91,6% (category best good). Study result that before get measure with avarage 62,25. Increase of cycle One with avarage become 70,00 with percentage 12,45%. To cycle two experience increase with average 81,50 with percentage 30,92%. Research result prove that application mode learning cooperatif type Snowball Trhowing can increase result study IPA Students class IIIA SD Negeri 011 Banjar XII Subdistrict Tanah Putih. Key Word : Cooperative Learning Mode Type Snowball Trhowing, Result Study IPA.